Longitudinal Assessment of Amyloid-β Deposition by [18F]-Flutemetamol PET Imaging Compared With [11C]-PIB Across the Spectrum of Alzheimer’s Disease - Hatashita, Shizuo; Wakebe, Daichi; Kikuchi, Yuki; Ichijo, Atsushi (Frontiers in Aging Neuroscience, 2019)
This study evaluates the longitudinal changes in the amyloid beta (Aβ) deposition with [18F]-flutemetamol (FMM) PET imaging across the spectrum of Alzheimer’s disease (AD), compared with [11C]-PIB PET. Eleven AD, 17 mild cognitive impairment (MCI) and 13 cognitively normal (CN) subjects underwent neuropsychological assessment and amyloid PET imaging using [18F]-FMM and [11C]-PIB during a follow-up period. Regions of interest were defined on co-registered MRI, and the FMM and PIB standardized uptake value ratio (SUVR) were used in the same cortical regions. Annual rate of change in FMM and PIB SUVRs was calculated. Cortical FMM SUVR in amyloid-positive subjects increased over a follow-up of 3.1±0.5 years, similar to PIB SUVR. Annual rate of increase in FMM SUVR was significantly greater in typical amyloid-positive (0.033±0.023, n=7), focal positive MCI (0.076±0.034, n=4) and positive CN (0.039±0.027, n=4) while that in AD (0.020±0.018, n=11) was smaller. An individual annual rate of change in FMM SUVR was correlated with that in PIB SUVR (r=0.69, n=41, p<0.01). The time of clinical progression of the disease was estimated at 7.2 years from the mean FMM SUVR of 1.32 in focal positive MCI patients to FMM SUVR of 1.87 in AD based on a mean 0.076 FMM SUVR increase per year. Our results suggest that the [18F]-FMM PET can clarify the longitudinal assessment of Aβ deposition, similar to [11C]-PIB PET. Increase in Aβ deposition is faster in the predementia stage of the AD spectrum. The amount and increase rate of Aβ deposition could provide a potential prognostic timeframe across AD spectrum.